Nonlinear optical probes for measuring membrane potential in neurons - Khadria, A (2017)
Chapter 1: In Chapter 1, I discuss the design and mechanisms of existing optical techniques to measure membrane potential of live cells. I compare the different fluorescence and second harmonic generation- based methodologies developed over the years to test voltage sensitivity of dyes. Chapter 2: I discuss the design, synthesis, and characterization of pyropheophorbide-based push-pull dyes as nonlinear optical probes. I show that the pyropheophorbides have different transition dipole moment for two-photon fluorescence and second harmonic generation in both 2D and 3D. Chapter 3: In this chapter, I investigate the cellular localization of different donor-acceptor porphyrin-based dyes in a multiphoton microscope. The dyes possess the same hydrophobic electron-donor group and porphyrin group but different hydrophilic electron-acceptor groups. The dyes stain different types of cellular organelles depending on the type of hydrophilic headgroups. Chapter 4: Here, I discuss the existing techniques to test voltage-sensitivity of organic dyes. I also discuss the design of a patch-clamp–based setup that I installed in the multiphoton microscope. I test the efficacy of the setup by testing the voltage sensitivity of commercial dyes. I also investigate the voltage sensing efficacy of plasma membrane bound porphyrinbased dyes. Chapter 5: In this chapter, I discuss the design, synthesis, and characterization of a new tricationic porphyrin-based dye, AK-1. I also investigate the plasma membrane localization of AK-1 in HEK 293T cells, U-87 MG cells, HeLa cells, rat hippocampal neurons, mice brain slices, contracting neonatal myocytes, gram negative bacteria E.Coli, and giant unilamellar vesicles. I demonstrate the voltage sensitivity of the dye in contracting neonatal myocytes. I also demonstrate multimodal imaging efficacy of AK-1. Chapter 6: In this chapter, I study the spatial characteristics of monocellular and multicellular spheroidal tumor models through two-photon microscopy. The spheroids display similar characteristics to real tumors.